An examination of three ethical perspectives on IT practitioners’ intentions to implement accessibility in IT artifact design - Mäkipää, Juho-Pekka; Naarmala, Jyri (RWTH Aachen, 2024)
Accessibility is a goal that information technology (IT) practitioners strive to achieve when creating IT artifacts for universal use. Designing accessible IT artifacts involves paradigms that encompass typical actions IT practitioners are expected to take. However, meeting user requirements within limited time and budget constraints is challenging and may raise ethical conflicts. In this paper secondary data from seven sample studies was analyzed and reasons why practitioners consider accessibility were collected. These collected views were then compared against three ethical theories: consequentialist ethics, deontological ethics, and virtue ethics to understand the ethical phenomena surrounding the accessibility design of IT artifacts. Preliminary findings suggest the three ethical perspectives seem connected to reasons influencing practitioners' intentions to implement accessibility. It seems that ethical conflict may occur in the relationship between intrinsic and extrinsic reasons. This paper encourages deeper discussion on the question of how to improve ethicality, guidance, and facilitation towards the right decisions in ethical dilemmas in IT artifact development.
Keywords: Digital accessibility; IT artifact design; ethics; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tuotantotalous|en=Industrial Management|